2020
DOI: 10.1093/jmammal/gyaa133
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific environmental conditions for winter bat acoustic activity in North Carolina, United States

Abstract: Low winter temperatures are a major driver of hibernation and migration in temperate North American bats. Hibernation and migration in turn affect bat mortality via white-nose syndrome and collisions with wind turbines. To describe winter bat acoustic activity across a wide temperature gradient and to understand species-specific responses to low temperatures, we recorded nightly acoustic activity of bats at 15 sites across the state of North Carolina, United States, from December through February 2016 – 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The big brown bat was associated with most seasons except for the winter, when the hoary bat was the dominant species. All seven species have been documented to be residents in the Piedmont of North Carolina for the winter [34,72]. However, we found that the big brown bat and the silver-haired bat were the most active species in the winter in non-urban settings instead of the hoary bat [72].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The big brown bat was associated with most seasons except for the winter, when the hoary bat was the dominant species. All seven species have been documented to be residents in the Piedmont of North Carolina for the winter [34,72]. However, we found that the big brown bat and the silver-haired bat were the most active species in the winter in non-urban settings instead of the hoary bat [72].…”
Section: Discussionmentioning
confidence: 54%
“…To understand how constructed wetlands affected the bat community, we first examined bat species richness at all seven sites. Previous research in our area suggested that weather conditions including temperature, wind, and precipitation could affect bat acoustic activities [62,64,72]. Thus, we extracted daily weather data (temperature in • C, wind in km/h, and precipitation in cm/h) from the source as described in Li et al (2020) [62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the sites were monitoring over a waterbody, which was recorded as a covariate for the statistical analysis. We also recorded site region as a covariate for the statistical analysis using the region classi cation described in Parker et al (2020). At each site, either a Wildlife Acoustics SM2 bat detector (Wildlife Acoustics, Inc, Concord, Massachusetts, United States) or an AnaBat SD2 bat detector (Titley Scienti c Inc., Australia) was used for acoustic monitoring.…”
mentioning
confidence: 99%